Decent work in Peru: conceptual framework and a proposal for measurement - Gamero Requena, Julio (2010)
Decent work is work that is available to anyone who wishes to work in conditions of freedom, equity, security and human dignity. There are ten categories for measuring decent work, the application of which makes it possible to determine the situation of a population with respect to its working conditions. The purpose of this article is to analyze the terms in which the labor standards incorporated in the respective chapter of the Free Trade Agreement with the United States have been complied with, one year after its application. To this end, a comparison of the labor indicators obtained before and after the signing of the FTA with the United States is offered.